Antibody–immunotoxin Conjugate Using FcBP-mediated Photoconjugation to Treat Cancer - Kim, Kwang Hyeok; Park, Jisoo; Kim, Jin Ock; Ko, Han Jik; Park, Sang Gyu (Anticancer Research, 2022)
Background/Aim: Cytotoxic payload conjugation to antibodies efficiently suppresses tumors and contributes to the improvement of cancer survival. In our previous study, c-Kit targeting antibody–drug conjugate (2G4-DM1) with DM1, a microtubule inhibitor, efficiently suppressed tumor growth. However, slow-growing c-Kit-positive tumors, such as GIST-48, did not efficiently respond to DM1. In this study, we aimed to treat tumors using 2G4 immunotoxin with Pseudomonas exotoxin A (PE) as a payload. Materials and Methods: Modified FcBP-PE24 containing p-benzoyl-L-phenylalanine, unnatural amino acid, was expressed in E. coli and purified. Then, photoconjugation of 2G4 antibody and FcBP-PE24 at 365 nm was carried out and 2G4 immunotoxin was purified using anion exchange chromatography. In vitro cytotoxicity of 2G4 immunotoxins was assessed in HMC-1.2, GIST-48, and MDA-MB-453 cells. Then, in vivo efficacy analysis was performed using C.B-17 SCID mice. Results: 2G4 immunotoxin efficiently induced cytotoxicity in 2G4-DM1–resistant HMC-1.2 and GIST-48 cells by inhibiting protein synthesis but not in c-Kit–negative MDA-MB-453 cells. The results showed ~200-fold or more increase in cytotoxicity against c-Kit–positive cells compared to IC50 of 2G4-DM1. In addition, 2G4 immunotoxin suppressed tumor growth in the in vivo xenograft mouse model. Conclusion: 2G4 immunotoxins could be an alternative therapeutic strategy for microtubule inhibitor–resistant cancer cells.
Keywords: Animals; Escherichia coli; Gastrointestinal Stromal Tumors; Humans; Immunoconjugates; Immunotoxins; Mice; Mice, SCID; antibody–drug conjugate; c-Kit; cancer; FcBP; immunotoxin